2019
DOI: 10.15244/pjoes/92817
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Antibacterial Activity of POMA Nanocomposites

Abstract: In this study, antibacterial activity of the prepared nanocomposites [poly (o-methoxy-aniline); POMA] at different concentrations was tested on bacterial strains. Nanocomposites were prepared by in situ chemical polymerization of ortho anisidine monomer in acidic medium with ammonium peroxydisulphate (APS) as an oxidant. The composition, structure and morphology of the polymer and nanocomposites were characterized by Fourier transform infrared spectroscopy (FTIR), x-ray diffraction (XRD) and ultraviolet-visibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…In this method, colloidal solution is formed which act as precursor and coagulated into NPs [29]. The size, structure, doping efficiency and many other characteristics are characterized by SEM, XRD, FTIR, UV/Visible spectroscopy, thermal gravimetric analysis (TGA) and transmission electron microscopy (TEM) [30][31][32][33][34][35][36][37]. Nanotechnology has makes immense applications in different fields.…”
Section: Npsmentioning
confidence: 99%
“…In this method, colloidal solution is formed which act as precursor and coagulated into NPs [29]. The size, structure, doping efficiency and many other characteristics are characterized by SEM, XRD, FTIR, UV/Visible spectroscopy, thermal gravimetric analysis (TGA) and transmission electron microscopy (TEM) [30][31][32][33][34][35][36][37]. Nanotechnology has makes immense applications in different fields.…”
Section: Npsmentioning
confidence: 99%
“…There are great number of secondary metabolites including anthocyanins, tannins, flavonoids, carotenoids, alkaloids, saponins and vitamin C etc. These are responsible for antimicrobial and antioxidant activities such as anti-allergic, anti-inflammatory and anti-thrombotic [1][2][3][4][5][6]. Bacteria have become more drug resistant due to excessive use of antibiotics in livestock, animal feed and aqua culture.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, ROS can react with protein, DNA, lipids, causing mutation and damage the cell membrane which results in tissue injuries. Research has revealed that ROS are involved in a number of disorders like Alzheimer, atherosclerosis, inflammation diabetes, cardiovascular and neurodegenerative diseases in human beings [3,5,19]. Antioxidants are responsible for certain types of cancer, aging process and offset harmful ROS.…”
mentioning
confidence: 99%
“…They improved the energy efficiency of photo generated supported various composition for appropriate co-catalysts. The atavistic has been improved at which the photocatalytic reaction occurs in which electrons moves to the holes from bulk to reaction active sites [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%